Endothelial glycocalyx and cardio-renal risk factors in type 1 diabetes - Stougaard, Elisabeth Buur; Winther, Signe Abitz; Amadid, Hanan; Frimodt-Møller, Marie; Persson, Frederik; Hansen, Tine Willum; Rossing, Peter (PloS one, 2021)
Glycocalyx lines the inner surface of the capillary endothelium. Capillaroscopy enables visualization of the sublingual capillaries and measurement of the Perfused Boundary Region (PBR) as an estimate of the glycocalyx. Novel software enables assessment of the PBR estimated at a fixed high flow level (PBR-hf) and an overall microvascular assessment by the MicroVascular Health Score (MVHS). Damaged glycocalyx may represent microvascular damage in diabetes and assessment of its dimension might improve early cardio-renal risk stratification. To assess the associations between PBR, PBR-hf and MVHS and cardio-renal risk factors in persons with type 1 diabetes (T1D); and to compare these dimensions in persons with T1D and controls. Cross-sectional study including 161 persons with T1D stratified according to level of albuminuria and 50 healthy controls. The PBR, PBR-hf and MVHS were assessed by the GlycoCheck device (valid measurements were available in 136 (84.5%) with T1D and in all the controls). Higher PBR and PBR-hf indicate smaller glycocalyx width. Lower MVHS represents a worse microvascular health. There were no associations between PBR, PBR-hf or MVHS and the cardio-renal risk factors in persons with T1D, except for higher PBR-hf and lower MVHS in females (p = 0.01 for both). There was no difference in PBR, PBR-hf or MVHS in persons with normo-, micro- or macroalbuminuria. The PBR was higher (2.20±0.30 vs. 2.03±0.18[mu]m; p<0.001) and MVHS lower (3.15±1.25 vs. 3.53±0.86[mu]m; p = 0.02) in persons with T1D compared to controls (p[less than or equal to]0.02). After adjustment for cardio-renal risk factors the difference in PBR remained significant (p = 0.001). The endothelial glycocalyx dimension was impaired in persons with T1D compared to controls. We found no association between the endothelial glycocalyx dimension and the level of albuminuria or cardio-renal risk factors among persons with T1D. The use of the GlycoCheck device in T1D may not contribute to cardio-renal risk stratification.